Tanggap Hasil Biji Bawang Merah Samosir aksesi Sagala Terhadap Konsentrasi GA3 dan Dosis Boron di Dataran Tinggi Samosir - Fajar Yandi Siahaan; Toga Simanungkalit; Mariati Mariati (Universitas Sumatera Utara, 2015)
The aim of the research was to identify the influence of GA3 Concentration and Dose of Boron on the seed yield of Samosir Shallot Sagala accesion. The research was conducted at Hatoguan Village, Subdistrict Palipi, Samosir, began from February until July 2014, using factorial randomized block design with two factors, replicated three times. The first factor was GA3 concentration (0, 50, 100, 150, 200 and 250 ppm) and the second was dose of boron (0, 1.5, 3 and 4.5 kg/ha). Parameters observed were percentage of flowering plants per plot, umbels number per plot, seeds weight per umbel and seeds weight per plot. The results showed that the percentage of flowering plants per plot was significantly affected by GA3 concentration, and seed weight per umbel by dose of boron. The highest percentage of flowering plants per plot was 41,27% produced by G4 (200 ppm GA3), and the corelation between dose of boron and seed weight per umbel showed positive linear regression. However all other parameters were not significantly affected by both treatments.Kata kunci : GA3 Concentration, Dose of Boron, Shallot